Use of fluoropolymers as release films in composite material molding methods

JP7936818B2Active Publication Date: 2026-10-16SYENSQO SA (50 00)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023565312
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-23
Filing Date
2022-04-21
Publication Date
2026-10-16
Estimated Expiration
2042-04-21

Smart Images

  • Figure 0007936818000001
    Figure 0007936818000001
Patent Text Reader

Abstract

The present invention relates to the use of a monolayer fluoropolymer film selected from ethylene tetrafluoroethylene and polytetrafluoroethylene films as a release film in a process for forming a composite material.
Need to check novelty before this filing date? Find Prior Art

Description

[Overview of the project]

[0001] Fiber-reinforced polymer composites are widely used in many industries, including aerospace, automotive, marine, industrial, construction, and a variety of consumer products, and are often preferred, especially in harsh environments, because they are lightweight while still exhibiting high strength and corrosion resistance. Fiber-reinforced polymer composites are typically manufactured either from pre-impregnated materials or through resin injection processes.

[0002] Pre-impregnated material, or "prepreg," generally refers to fibers (such as carbon fibers) impregnated with a curable matrix resin (such as epoxy). The resin content in prepregs is relatively high, typically 40% to 65% by volume. Multiple plies of the prepreg can be cut to size for lamination, then assembled and molded with a molding tool. If the prepreg cannot be easily conformed to the shape of the molding tool, heat may be applied to the prepreg to gradually deform it to the shape of the molding surface. Fiber-reinforced polymer composites can also be manufactured by liquid molding processes, including resin injection techniques. In a typical resin injection process, dry fibers bound with a binder are placed in a mold as a preform, and then a liquid matrix resin is injected (injected or infused) directly in place. After injection (or infusion), the resin-injected preform is cured to obtain a finished composite article.

[0003] For both types of materials, the three-dimensional shaping (or molding) process of composite materials is critical to the appearance, properties, and performance of the final molded product. While it remains common practice to shape preforms into intricate forms using hand lay-up processes, this is time-consuming and often results in significant part-to-part variability. Other, less manual methods exist for molding composite materials (such as vacuum forming, which may utilize pins, robots, and / or actuators to assist in part formation), but such methods have their own drawbacks and disadvantages. In addition, such methods are often time-consuming and do not take into account the rheological behavior and curing properties of the composite material. Furthermore, products produced by such processes still tend to have wrinkles and other defects.

[0004] Given the potential drawbacks of composite material processing, such as processing time, part-to-part variability, and product contamination, there remains a need to develop faster, improved, and more reliable assemblies and processes. It is also desirable to consider rheological behavior and curing properties, and, where possible, to provide processes that maximize the use of existing equipment (e.g., metal stamps or presses).

[0005] A method for forming composite materials using a double diaphragm mechanical thermoforming process has been successfully developed with the aim of providing an assembly for isolating composite materials from environmental pollutants, and a forming process that not only addresses the shortcomings and disadvantages of other methods known in the art, but also takes into account the rheological behavior and curing properties of the composite material, and also allows the use of existing infrastructure and equipment. This method provides an effective and efficient means for automatically manufacturing complex three-dimensional composite structures. Thus, three-dimensional composite structures can be manufactured rapidly, repeatedly, and on a large scale.

[0006] For example, this illustrates how this double diaphragm formation technology has developed rapidly and made it possible to use it for full-scale automobile production.

[0007] The use of composite materials in the automotive market continues to increase due to the ever-growing need for lighter components. Therefore, original equipment manufacturers (OEMs) are increasingly shifting towards manufacturing technologies with speed capabilities, such as compression molding, to meet future speed and weight targets.

[0008] However, current solutions often fail to achieve both the required curing temperature range and the desired surface quality of the components. Consequently, composite components, particularly for visual or Class A applications, require additional modifications to meet the standards expected by the automotive industry.

[0009] The method using a double diaphragm mechanical process implements a diaphragm. In this context, the term “diaphragm” refers to any barrier that divides or separates two different physical areas. The term “diaphragm structure” is also used to refer to an assembly of one or more diaphragms that define an external space and an isolated internal space, for example, an area within an encapsulation pocket and an area outside the encapsulation pocket. Generally, the materials used to manufacture the diaphragm are not particularly limited and may be, for example, rubber, silicone, plastic, thermoplastic resin, or similar materials, or may include a film selected from a plastic layer or an elastic layer. The diaphragm may consist of a single material or may include, for example, multiple materials arranged in layers.

[0010] Films used as diaphragms exist and consist of one or more layers. However, these films may have considerable limitations and may have lower performance that can hinder their use. In particular, these include both a limited curing temperature range (<150°C) and the achievable surface quality of the components, and therefore, the curing speed for mass production, particularly in a range of automotive or aerospace applications, and the inability to fully utilize the rate capabilities of some fast-curing epoxy systems due to high-temperature curing (<190°C). For example, this includes a given T temperature range of about 150 to about 200°C. 硬化 This can cause the film to melt and / or break during the formation of composite components.

[0011] Furthermore, certain release layers soften when processed above their melting temperature, increasing the likelihood of print-through and / or orange peel effects on the cured part surface. Some unbalanced multilayer compositions in films also cause film curling during assembly, limiting process robustness and usability.

[0012] Furthermore, multilayer films are not very user-friendly. In particular, certain existing films with unbalanced multilayer compositions also cause film curling during assembly, limiting process robustness and usability. Moreover, the use of multilayer films limits the possibility of recycling these films or at least requires the setup of more complex and costly processes.

[0013] Therefore, there remains a need for a film that allows for both higher temperature part hardening (≤200°C) and significantly reduced process cycle time, while simultaneously improving the appearance of parts directly from the mold, and exhibiting a wide temperature range used in high-temperature double-diaphragm mechanical processes for forming structural composite components. The result is a reduction in overall part manufacturing cycle time and cost associated with intermittent reworking and repair.

[0014] In addition to these requirements, one of the desired properties of these films is their self-peeling ability. However, at high temperatures, the films may have the disadvantage of sticking to composite components, which can particularly lead to a degraded surface finish.

[0015] This disclosure addresses these drawbacks by providing the use of specific films in a method using a double-diaphragm mechanical thermoforming process for forming composite materials—both individually and together.

[0016] The applicant has discovered that the use of a single-layer fluoropolymer film, selected from ethylene tetrafluoroethylene (ETFE) film and polytetrafluoroethylene (PTFE) film, as a release film for high-temperature double diaphragm formation (DDF) makes it possible to obtain composite components with complex structures that can be used over a wide temperature range and are therefore suitable for use as diaphragms. In addition, this fluoropolymer film, selected from ETFE and PTFE films, enables both higher temperature part curing and significantly reduced process cycle time, while simultaneously improving the appearance of parts directly from the mold.

[0017] Furthermore, this fluoropolymer film, selected from ETFE and PTFE films, has the advantage of being easily self-peelable, which allows for no migration and / or contamination from the composite material to the film and / or from the film to the composite material after curing.

[0018] Accordingly, the present invention relates to the use of a single-layer fluoropolymer film selected from ETFE film and PTFE film as a release film in a method for forming a composite material, wherein the method is (a) A step of placing a substantially planar composite material between films by creating a pocket for housing the composite material between the upper fluoropolymer film and the lower fluoropolymer film, (b) The process of bringing the upper fluoropolymer film and the lower fluoropolymer film into close contact with the composite material, thereby forming a layered structure, wherein the composite material is held immobile between the upper fluoropolymer film and the lower fluoropolymer film until heat or force is applied to the layered structure; (c) Optionally, preheating the layered structure in a heating device to a temperature sufficient to either reduce the viscosity of the composite material or to soften the film; (d) A step of arranging a layered structure in a press tool including a male mold and a corresponding female mold separated by a gap, wherein the male mold and the female mold each independently have a non-planar molding surface, (e) The process of compressing the layered structure between the male and female molds by closing the gap between them; and (f) The process of keeping the male and female molds closed until the viscosity of the layered structure reaches a level sufficient to maintain the molded shape. including Regarding use.

[0019] The upper fluoropolymer film and the lower fluoropolymer film can be independently selected from ETFE film and PTFE film. For example, in some embodiments, the lower film may be an ETFE film and the upper film may be a PTFE film. Similarly, for example, in some embodiments, the lower film may be a PTFE film and the upper film may be an ETFE film. However, in preferred embodiments, the fluoropolymer used for the upper and lower films is the same, namely either an ETFE film or a PTFE film. In some embodiments, an ETFE film is used as both the upper and lower film. In other embodiments, a PTFE film is used as both the upper and lower film.

[0020] According to the present invention, the fluoropolymer film selected from ETFE films and PTFE films is self-releasing. That is, the film can be easily peeled from the final molded composite part and / or the molded assembly can be easily peeled from the tooling. This provides distinct advantages of tooling protection, such as reduced tool wear, and zero requirement for mold sealant or release agent application between molded parts, reduced contact work and final part cost, and thus facilitates full-scale composite structure production.

[0021] Typically, the ETFE film used in the present invention comprises at least about 99% by weight, particularly at least about 99.5% by weight of ethylene tetrafluoroethylene. The ETFE film may also contain polymer additives such as thermal stabilizers or processing stabilizers, antistatic agents, and lubricants.

[0022] Typically, the PTFE film used in the present invention comprises at least about 99% by weight, particularly at least about 99.5% by weight of polytetrafluoroethylene. The PTFE film may also contain polymer additives such as thermal stabilizers or processing stabilizers, antistatic agents, and lubricants.

[0023] According to the present invention, the fluoropolymer film selected from ETFE films and PTFE films is used for high temperature double diaphragm forming (DDF) of complex composite structures using a press. This film has a wide curing temperature range, i.e., about 120 to about 200°C corresponding to automotive market standards, especially about 120 to about 170°C, particularly 120 to about 150°C, as well as a curing temperature T of about 150 to about 190°C, particularly about 160 to about 190°C corresponding to aerospace and UAM market standards 硬化 has the advantage of being usable over a range.

[0024] Thus, the fluoropolymer film selected from ETFE films and PTFE films used as a release film in the present invention exhibits unique properties.

[0025] A given curing temperature T including about 120 to about 200°C 硬化 can ensure that the film is free of melting and / or breakage and has proper release performance throughout the formation of the composite component. Therefore, in some embodiments, the fluoropolymer film selected from ETFE films and PTFE films has a melting temperature of about 240°C or higher. In some embodiments, particularly the ETFE film has a melting temperature of about 240°C or higher. In some embodiments, particularly the PTFE film has a melting temperature of about 300°C or higher.

[0026] In some embodiments, the thickness (t) of the fluoropolymer film selected from ETFE films and PTFE films, which depends on the shape of the composite component, ranges from about 10 microns to about 200 microns, in particular from about 20 microns to about 150 microns. Preferably, the film has a thickness of about 30 microns to about 100 microns. In some embodiments, in particular, the thickness (t) of the ETFE film ranges from about 30 microns to about 100 microns, preferably from about 50 microns to about 80 microns. In some embodiments, in particular, the thickness (t) of the PTFE film ranges from about 30 microns to about 100 microns. This thickness makes it possible to obtain the desired mechanical performance of the film, and prevent film wrinkling during preheating and breakage during composite component formation.

[0027] In some embodiments, a fluoropolymer film selected from ETFE and PTFE films has an elastic modulus (E) in the range of about 300 to about 950 MPa, preferably about 350 to about 900 MPa, and a tensile strength (σ) in the range of about 30 to about 90 MPa, preferably about 35 to about 80 MPa. In some embodiments, in particular, the ETFE film has an elastic modulus (E) in the range of about 500 to about 900 MPa, preferably about 550 to about 800 MPa, and a tensile strength (σ) in the range of about 45 to about 90 MPa, preferably about 50 to about 65 MPa. In some embodiments, in particular, the PTFE film has an elastic modulus (E) in the range of about 300 to about 500 MPa, preferably about 350 to about 450 MPa, and a tensile strength (σ) in the range of about 30 to about 55 MPa, preferably about 35 to about 50 MPa. This can help prevent film breakage during composite component formation.

[0028] Ensuring the desired shape of the component is achieved by a given T temperature range including approximately 120 to 200°C. 硬化 This can be achieved without film breakage during formation, and the film used in the present invention has a specific elongation at break (ε). In some embodiments, a fluoropolymer film selected from ETFE film and PTFE film exhibits an elongation at break (ε) in the range of about 400 to about 700%, particularly about 450 to about 650%, in either the longitudinal or transverse direction at a rate of about 8 mm / s under ambient conditions, where typically, the ambient temperature is T 周囲 The temperature is approximately 20 to 25°C. In some embodiments, the ETFE film in particular exhibits a break elongation (ε) in the range of approximately 400 to 700%, particularly 450 to 600%, in either the longitudinal or transverse direction at a speed of approximately 8 mm / second under ambient conditions. In some embodiments, the PTFE film in particular exhibits a break elongation (ε) in the range of approximately 400 to 700%, particularly 450 to 650%, in either the longitudinal or transverse direction at a speed of approximately 8 mm / second under ambient conditions.

[0029] To avoid limiting the size of composite components, such films have a sufficiently large width. In some embodiments, the product width of the fluoropolymer film, selected from ETFE and PTFE films, is about 1.2 m or more. Preferably, this product width is about 1.5 m or more.

[0030] Thus, in preferred embodiments, the fluoropolymer film selected from ETFE film and PTFE film used according to the present invention is - Melting temperature of approximately 240°C or higher (T 溶融 ), - Thickness (t) in the range of approximately 10 microns to approximately 200 microns, especially approximately 20 microns to approximately 150 microns, and particularly approximately 30 microns to approximately 100 microns. - Modulus of elasticity (E) in the range of approximately 300 to approximately 950 MPa, preferably in the range of approximately 350 to approximately 900 MPa. - Tensile strength (σ) in the range of approximately 30 to approximately 90 MPa, preferably in the range of approximately 35 to approximately 80 MPa, and - Under ambient conditions, the elongation at fracture (ε) is approximately 400-700% in either the longitudinal or transverse direction, particularly in the range of approximately 450-650%, at a speed of approximately 8 mm / second. It holds.

[0031] In another preferred embodiment, the ETFE film used according to the present invention is - Melting temperature of approximately 240°C or higher (T 溶融 ), - Thickness (t) in the range of approximately 30 microns to approximately 100 microns, preferably 50 microns to approximately 80 microns. - Modulus of elasticity (E) in the range of approximately 500 to approximately 900 MPa, preferably in the range of approximately 550 to approximately 800 MPa. - Tensile strength (σ) in the range of approximately 45 to approximately 90 MPa, preferably in the range of approximately 50 to approximately 65 MPa, and - Under ambient conditions, elongation at fracture (ε) is approximately 400-700% in either the longitudinal or transverse direction, particularly in the range of approximately 450-600%, at a speed of approximately 8 mm / second. It holds.

[0032] In another preferred embodiment, the PTFE film used in accordance with the present invention is - Melting temperature of approximately 300°C or higher (T 溶融 ), - Thickness (t) in the range of approximately 30 microns to approximately 100 microns. - Modulus of elasticity (E) in the range of approximately 300 to approximately 500 MPa, preferably in the range of approximately 350 to approximately 450 MPa. - Tensile strength (σ) in the range of approximately 30 to approximately 55 MPa, preferably in the range of approximately 35 to approximately 50 MPa, and - Under ambient conditions, the elongation at fracture (ε) is approximately 400-700% in either the longitudinal or transverse direction, particularly in the range of approximately 450-650%, at a speed of approximately 8 mm / second. It holds.

[0033] Film thermal properties such as melting temperature can be measured using differential scanning calorimetry (DSC) in accordance with ASTM D3418, for example, by using a differential scanning calorimetry instrument such as the TA Instruments Q2000.

[0034] The mechanical properties of the film, such as tensile strength, tensile modulus, and elongation at break, can be measured using the Thin Film Tensile Strength & Elongation test (ZM45) in accordance with ASTM D882-09, for example, by using a Zwick Z250 testing machine.

[0035] Typically, ETFE and TFE are thermoplastic fluoropolymers that can be obtained by methods known in the art. For example, ETFE can be processed using standard thermoplastic processing methods such as injection molding, compression molding, blow molding, rotational molding, extrusion, and wire coating. Furthermore, for example, ETFE films can be obtained by blow molding or extrusion lamination techniques. In addition, for example, PTFE films can be obtained by casting, die extrusion, or skiving. Such methods are known to those skilled in the art.

[0036] According to embodiments of the present invention, the ETFE film can be recycled and reused in a method of forming a composite material as claimed in the present invention. For example, once a used ETFE film is peeled from the final composite material, the film can be granulated and then extruded in an extruder typically known in the art to obtain a new film, which can be used in a method of forming a composite material, particularly in the manner described above.

[0037] As used herein, the term “substantially planar” refers to a material having one plane that is significantly larger than the other two planes (e.g., at least two, three, four, or five times larger, or more). In some embodiments, a substantially planar material has thickness variation along the largest plane. For example, a composite material may include pad-up (i.e., a localized increase in the amount of ply) or ply-drop (i.e., a localized decrease in the amount of ply), material variations, and / or reinforcing materials such as areas where the composite material transitions to fabric. In other embodiments, a substantially planar material exhibits minimal thickness variation along the area of ​​the composite material. For example, the term substantially planar may mean that a composite material has an overall thickness variation of ±15% or less over 90% of its area. In some embodiments, the thickness variation is ±10% or less over 90% of its area. Substantially planar is not intended to mean a material that is perfectly flat, and also includes materials with slight variations in concave and / or convex surfaces.

[0038] In connection with the present invention, the method for forming the composite material can be either a framed assembly or a frameless assembly. In some embodiments, the method includes the use of a framed assembly. The upper and lower films are held together by a structural frame including an upper frame, a middle frame, and a bottom frame, where, The lower film is held between the bottom frame and the central frame. The upper film is held between the central frame and the top frame.

[0039] In a preferred embodiment, the method includes the use of a framed assembly.

[0040] In certain embodiments, the pocket containing the composite material is defined by a structural frame that houses the composite material held between the films. In certain embodiments, a substantially planar composite material is placed between an upper film and a lower film. This creates a pocket between the films that houses the composite material. For example, a lower file having a top and a bottom surface can be placed such that its bottom surface contacts the top of the outer periphery of the bottom frame. The composite material can then be placed on the top of the lower film; the central frame can be placed on the top surface of the lower film, then the upper film, and finally the top frame in contact with the upper film. This arrangement forms a pocket between the lower and upper films that houses the composite material layer. In some embodiments, the central frame may be omitted. The top, central (if present), and bottom frames define the periphery that maintains the shape of the fluoropolymer film according to the present invention, for example, by the arrangement of clamps or other fastening means at predetermined intervals around the periphery. Such top, central, and bottom frames can be manufactured based on the size and shape of the composite material to be molded. Optionally, pre-fabricated structural support frames are known in the art for use in conjunction with conventional metal or composite press tools (e.g., those manufactured by Langzauner or Schubert).

[0041] In some embodiments, the central frame may include means for removing air, such as a vacuum port or other valve. The vacuum port, if present, is connected to a vacuum source (e.g., a vacuum pump). In some embodiments, the pockets containing the composite material may be sealed pockets, such as air-sealed pockets, so that the structural frame is positioned around the entire perimeter of the composite material, preventing air or contaminants from entering the pockets.

[0042] The upper and lower films are brought into close contact with the composite material to form a layered structure. This can be achieved, for example, by applying vacuum pressure between the upper and lower films. In other embodiments, this can be achieved by physically applying pressure (e.g., manually or mechanically) to the upper and / or lower films to remove air. Vacuum pressure is desirable in certain cases, for example, to remove most of the residual air that may interfere with molding performance, thus minimizing deformation or wrinkling of the composite material (or its components). Vacuum also prevents film wrinkling and adds stability to the overall assembly. The use of vacuum pressure also helps maintain fiber alignment, supports the material during the process and molding, and / or maintains the desired thickness at high temperatures. The term “vacuum pressure” as used herein refers to a vacuum pressure of less than 1 atmosphere (or less than 10¹³ mbar). In some embodiments, the vacuum pressure between the films is set to less than about 1 atmosphere, less than about 800 mbar, less than about 700 mbar, or less than about 600 mbar. In some embodiments, the vacuum pressure between the films is set to approximately 670 mbar. At this point, the composite material is held firmly between the films, whether by vacuum or by other means, such as mechanical means, so that it remains immobile until heat and / or force is applied. Such an immobile layered structure can be advantageous, for example, because the composite material held within the layered structure is not only maintained immobile in its position with sufficient tension across the X and Y axes, but it can also be indexed. That is, the composite material may be placed (e.g., by automated means) at a specific position between the films within the immobile layered structure. This indexed immobile layered structure may then be placed (e.g., by automated means) at a specific position on the press tool (as described in more detail below herein) so that the press tool consistently engages with a given area of ​​the composite material. Thus, the immobile layered structure can be reliably used to produce multiple copies of a molded product without the need to individually index each composite material blank.

[0043] In some embodiments, the composite material can be machined according to the pattern before step (a).

[0044] In some cases, layered structures can be preheated in a heating device. The layered structures can be placed in the heating device manually or by automated means, such as using an automated shuttle. The heating device can be any heater usable in forming or shaping metal or composite products, such as a contact heater or a non-contact heater (i.e., a ceramic heater or an infrared (IR) heater). In some cases, this preheating softens the upper and lower films, for example, so that they are more flexible during the formation of the final molded product. In some cases, this preheating brings the composite material held within the layered structure to a desired viscosity or temperature, allowing complex shapes to be formed from a flat initial layup. Preheating can occur in a heating device heated to temperatures above approximately 75°C, 100°C, 125°C, 150°C, 175°C, or 190°C. This temperature can be adjusted, for example, depending on the identity of the components in the composite material. Such preheating is advantageous, for example, when it is desirable to minimize the heating of the press tool and / or the amount of time the layered structure is inside the press tool.

[0045] To form the final molded product, the layered structure is placed in a press tool. In some embodiments, no vacuum pressure is applied to any part of the press tool. In other embodiments, a localized vacuum is applied to the tool surface, for example, to remove air trapped between the layered structure and the tool. However, in such embodiments, the vacuum is not typically used as a force to form the shape of the final molded product. The layered structure can be placed in the press tool manually or by automated means, such as using an automated shuttle. This press tool generally includes a male and female mold, separated by a gap. Each mold has a non-planar molding surface. In some embodiments, a release agent may be added to the male, female, or both. Such a release agent may be useful, for example, to remove the molded part from the mold while it is still above ambient temperature. In some embodiments, a release agent is not required. The molding surfaces are fixed, i.e., not reconfigurable. The molding surfaces are also typically matched, i.e., the male mold roughly corresponds to the female mold in reverse; in some embodiments, they may be perfectly matched. However, in some embodiments, the male and female molds are such that the thickness between them changes when closed. In certain embodiments, the layered structure is placed in the gap between the male and female molds at a specific, predetermined distance.

[0046] Next, the layered structure is compressed between the male and female molds by closing the gap between the molds (step (e)). In some embodiments, this is achieved by partially closing the gap between the male and female molds to form a smaller gap between the molds. This smaller gap is then closed after a certain time or viscosity is reached. "Closing the gap" is understood to mean compressing the molds along the Z-axis so that a predetermined final cavity thickness is obtained between the molds. The final cavity thickness can be adjusted, for example, by controlling where the molds stop relative to each other, and the choice of thickness can be made by the mold operator and will depend on the properties of the final molded product. In some embodiments, the final cavity thickness is substantially uniform, i.e., the process produces a double-faced molded final product in which the thickness varies by less than 5%. In some embodiments, the process produces a final molded product in which the thickness varies by only about 4%, e.g., less than 3%, less than 2%, or even less than 1%. In other embodiments, the male and female tools may be arranged and configured to give a cavity thickness that intentionally varies across the X and Y axes.

[0047] In certain embodiments, the male and female molds are maintained at a temperature above ambient temperature. For example, they may be maintained at temperatures above approximately 75°C, 100°C, 125°C, 150°C, 175°C, 200°C, or even higher, particularly, for example, between approximately 120°C and 200°C. This temperature can be adjusted depending on the identity (as well as viscosity and reactivity) of the components in the composite material. The molds can be maintained at a temperature above the softening point of the binder or matrix material used in the composite material, for example. In some embodiments, the composite material includes a thermosetting material, and the molds are maintained at a temperature of approximately 100°C to 200°C. The binder or matrix material in the composite material is in a solid phase at ambient temperature (20°C to 25°C), but will soften when heated. This softening allows for the molding of the composite material with a press tool and the fitting of a flat preform to the shape of the final component.

[0048] In some embodiments, the male mold and the female mold are maintained in a closed position for a predetermined period of time to form a molded structure. For example, in some embodiments, the mold is heated and maintained in the closed position until a desired viscosity or temperature is reached. In some embodiments, the mold is maintained in the closed position until the viscosity of the composite material is about 1.0×10 8 less than mPa. In some embodiments, the mold is heated and maintained in the closed position until the binder or matrix material begins to crosslink. In other embodiments, the mold is not heated, but is maintained in the closed position for a time sufficient for the material to retain its molded shape. The mold may be maintained in the closed position for 1 minute to about 60 minutes, for example about 5 to about 20 minutes, or for example about 1 to about 10 minutes. The length of time that the mold is maintained in the closed position will depend on many factors, such as the identity of the composite material and the temperature of the mold.

[0049] In certain embodiments, the male mold is moved through the layered structure, while the female mold remains stationary. In other specific embodiments, the female mold is moved through the layered structure, while the male mold remains stationary. In other embodiments, the female mold does not remain stationary, but moves at a slower speed than the male mold (such that the male mold still primarily functions as a forming surface). In still other embodiments, both molds move at approximately the same speed to close the gap between the molds. The molds are moved at a speed sufficient to deform / mold the composite material into a desired shape and to a final pressure. For example, the molds may be moved at a speed of about 0.4 mm / sec to about 500 mm / sec, for example about 0.7 mm / sec to about 400 mm / sec, particularly about 1 mm / sec to about 350 mm / sec, for example 5 mm / sec to 350 mm / sec, or about 50 mm / sec to 300 mm / sec. Moreover, the molds may be moved to a final pressure of about 30 psi to about 1000 psi, particularly about 100 psi to about 800 psi, or about 250 psi to about 750 psi. In some embodiments, the molds are moved at a selected speed and to a final pressure to control the thickness of the final molded product while avoiding wrinkle formation and structural fiber strain. In addition, the molds may be moved at a selected speed and to a final pressure to enable rapid formation of the final molded part.

[0050] Next, a gap is created between the male and female molds. While the molded structure remains on the press tool, it may be cooled below the glass transition temperature of the binder or matrix material. However, in some embodiments, the molded structure is removed from the press tool before it cools below the glass transition temperature of the binder or matrix material. All molded structures are removed more easily from the press tool thanks to the use of the fluoropolymer release film of the present invention. If the binder or matrix material cools below its glass transition temperature, the binder or matrix material returns to a solid phase, and the composite material retains its newly formed shape. If the composite material is a preform, such a preform will retain its desired shape for subsequent resin injection.

[0051] Once the molded structure is obtained, the clips and / or fasteners are loosened and the different frames are removed from the film. The film and cured composite components are then removed, and the film is peeled away from the cured composite components.

[0052] According to the present invention, the fluoropolymer film selected from ETFE film and PTFE film is self-peelable. Thus, the film can then be easily peeled from the final molded part to obtain an excellent display surface finish of the cured composite part after curing, without any signs of surface porosity or weave distortion, while simultaneously limiting fabric print-through and orange peel effect to a reasonably practical degree.

[0053] Furthermore, if necessary, the film can be temporarily maintained on the final molded product. For example, a temporary film may be desirable to protect components from environmental factors such as contamination before further processing, i.e., finishing / painting.

[0054] As used herein, the term “composite material” refers to an assembly of structural fibers and a binder or matrix material. The structural fibers may be organic fibers, inorganic fibers, or mixtures thereof, including, for example, commercially available structural fibers such as carbon fibers, glass fibers, aramid fibers (e.g., Kevlar), high-modulus polyethylene (PE) fibers, polyester fibers, poly-p-phenylene-benzobisoxazole (PBO) fibers, quartz fibers, alumina fibers, zirconia fibers, silicon carbide fibers, other ceramic fibers, basalt, natural fibers, and mixtures thereof. It should be noted that end applications requiring high-strength composite structures will typically utilize fibers with high tensile strength (e.g., ≥3500 MPa or ≥500 ksi). Such structural fibers may comprise one or more layers of fibrous material in any conventional configuration, such as, for example, unidirectional tape (UniTape) webs, nonwoven mats or bales, woven fabrics, knitted fabrics, non-crimped fabrics, fiber tows, and combinations thereof. It should be understood that structural fibers may be included as one or more plies throughout all or part of the composite material, or in the form of pad-ups or ply drops, resulting in localized increases / decreases in thickness.

[0055] The fibrous material is held and stabilized in place by a binder or matrix material so that the arrangement of the fibrous material is maintained and the stabilized material can be stored, transported, and handled (e.g., molded or otherwise deformed) without fraying, unraveling, tearing, buckling, wrinkling, or otherwise loss of integrity of the fibrous material. Fibrous material held by a small amount of binder (e.g., typically less than about 10% by weight) is typically called a fibrous preform. Such preforms would be suitable for resin injection applications such as RTM. The fibrous material may also be held by a large amount of matrix material (referring to matrix-impregnated fibers, commonly called a “prepreg”), and thus would be suitable for final product formation without further addition of resin. In certain embodiments, the binder or matrix material is present in the composite material in amounts of at least about 30%, at least about 45%, at least about 40%, or at least about 45%.

[0056] Binder or matrix materials are generally selected from thermoplastic polymers, thermosetting resins, and combinations thereof. When used to form preforms, such thermoplastic polymers and thermosetting resins can be introduced in various forms, such as powders, sprays, liquids, pastes, films, fibers, and nonwoven veils. Means of utilizing these various forms are generally known in the art.

[0057] Examples of thermoplastic materials include polyester, polyamide, polyimide, polycarbonate, poly(methyl methacrylate), polyaromatic compounds, polyesteramide, polyamideimide, polyetherimide, polyaramid, polyarylether ketone, polyetherether ketone, polyetherketone ketone, polyacrylate, poly(ester)carbonate, poly(methyl methacrylate / butyl acrylate), polysulfone, polyarylsulfone, copolymers thereof, and combinations thereof. In some embodiments, the thermoplastic material may also contain one or more reactive end groups, such as amine or hydroxyl groups, that react with an epoxide or curing agent.

[0058] Examples of thermosetting materials include epoxy resins, bismaleimide resins, formaldehyde condensation resins (including formaldehyde-phenol resins), cyanate resins, isocyanate resins, phenol resins, and mixtures thereof. The epoxy resin may be a mono or polyglycidyl derivative of one or more compounds selected from the group consisting of aromatic diamines, aromatic monoprimary amines, aminophenols, polyhydric phenols, polyhydric alcohols, and polycarboxylic acids. The epoxy resin may be polyfunctional (e.g., bifunctional, trifunctional, and tetrafunctional epoxy).

[0059] In some embodiments, combinations of thermoplastic polymers and thermosetting resins are used in composite materials. For example, certain combinations may work synergistically with respect to flow control and flexibility. In such combinations, the thermoplastic polymer will provide flow control and flexibility to the blend, which will typically be superior to the low-viscosity, brittle thermosetting resin.

[0060] The use of the specific fluoropolymer film described above not only aids in the molding of composite materials by, for example, maintaining the composite material in a fixed position with sufficient tension across its X and Y axes, but also provides significant additional functional advantages. For instance, this arrangement protects the composite material blank from environmental contaminants, such as impurities in the air or on tooling machines. This protection enables the use of conventional press tools (which would otherwise be cumbersome) for processing two-dimensional preforms into complex three-dimensional shapes, thus allowing for significantly more complex three-dimensional shapes than either vacuum forming or reconfigurable tooling techniques. Furthermore, the use of a double diaphragm arrangement can allow the demolding process to be eliminated from the overall process.

[0061] The double diaphragm mechanical thermoforming process described herein provides an effective and efficient means of automatically manufacturing complex three-dimensional composite structures from two-dimensional flat preforms, which is suitable for both the automotive, UAM, and aerospace markets. Three-dimensional composite structures can be manufactured rapidly, repeatedly, and on a large scale. For example, three-dimensional composite structures can be formed from substantially planar composite material blanks in 1-10 minute cycles, 5-20 minute cycles, 10-30 minute cycles, or 20-60 minute cycles, depending on the desired part and composite material identity. Such a rapid, repeatable process is suitable for manufacturing automotive parts and panel materials such as hoods, trunks, door panels, fenders, and wheel wells. [Examples]

[0062] The following examples are for illustrative purposes only and should not be construed as limiting the scope of the attached claims.

[0063] Example 1: Double diaphragm mechanical thermoforming with frame using high-temperature ETFE film and fast-curing automotive epoxy prepreg. A downwardly flexible diaphragm made of a 52-micron ETFE film was placed on a base plate that held the bottom frame. This film exhibits the characteristics reported in Table 1.

[0064] [Table 1]

[0065] A composite material blank and surface film (Solvay, formerly Cytec Industries, VTF266) made of carbon fiber reinforced epoxy (Solvay, formerly Cytec Industries, MTM58B) were placed on top of the lower flexible diaphragm, followed by a central frame with a vacuum port. Next, an upper flexible diaphragm made of the same film as the lower flexible diaphragm was placed so that it covered the central frame and the composite material blank. The top, central, and bottom frames were fixed together, thereby creating a vacuum airtight seal and an enclosed pocket surrounded by the lower flexible diaphragm, upper flexible diaphragm, and central frame. Vacuum was then drawn until the vacuum pressure reached a maximum of 670 mbar to remove air from between the upper and lower flexible diaphragms. At that point, the composite material blank was firmly supported by both diaphragms, creating a non-moving layered structure.

[0066] Next, the layered structure was moved by shuttle into a non-contact heating device, where it was heated to 140°C. As soon as the outer film temperature reached a maximum of 120°C, it was moved by shuttle into a press tool containing a matched male and female mold configured to the shape of a structural automotive Class A demonstrator component. The female mold was then moved toward the male mold at a speed of approximately 4 mm / second (250 mm / second). The female mold was left stationary, and both molds were held at 150°C until crosslinking began. The molded structure was removed from the press tool while still hot and allowed to cool after removal. The process of molding the composite blank took 15 minutes from start to finish (i.e., from the initial placement of the lower flexible diaphragm to the establishment of the final shape).

[0067] After demolding and cooling, parts manufactured using a 52-micron ETFE top film were visually inspected and scanned using short-wave and long-wave scanning techniques (Visuol) to check the levels of orange peel (fine) and fabric print-through (coarse), respectively. The results clearly show that the improved thermal performance and film rigidity of the ETFE top film enabled a significant reduction in the measured print-through and orange peel.

[0068] The thermal properties of the film were measured using differential scanning calorimetry (DSC) with a TA Q2000 DSC instrument according to ASTM 3418. A heating / cooling / heating procedure was applied, and the temperature range of -30°C to 300°C was screened at a cooling and heating rate of 10°C / min.

[0069] The mechanical properties of the film were measured according to ASTM D882-09 using a Zwick Z250 tester. The film was tested in both the longitudinal and transverse directions at a test speed of approximately 8 mm / second (500 mm / min) under ambient conditions of 23°C and 50% relative humidity.

Claims

1. The use of a single-layer fluoropolymer film selected from ethylene tetrafluoroethylene film and polytetrafluoroethylene film as a release film in a method for forming composite materials, wherein the method is (a) A step of placing a substantially planar composite material between the upper fluoropolymer film and the lower fluoropolymer film by creating a pocket for containing the composite material between the upper fluoropolymer film and the lower fluoropolymer film, (b) The step of bringing the upper fluoropolymer film and the lower fluoropolymer film into close contact with the composite material, thereby forming a layered structure, wherein the composite material is held immobile between the upper fluoropolymer film and the lower fluoropolymer film until heat or force is applied to the layered structure; (c) optionally preheating the layered structure in a heating device to a temperature sufficient to either reduce the viscosity of the composite material or to soften the film; (d) A step of placing the layered structure in a press tool including a male mold and a corresponding female mold separated by a gap, wherein the male mold and the female mold each independently have a non-planar molding surface, (e) a step of compressing the layered structure between the male and female molds by closing the gap between the male and female molds; and (f) The step of keeping the male and female molds in the closed position until the viscosity of the layered structure reaches a level sufficient to maintain the molded shape. Uses including, The upper fluoropolymer film and the lower fluoropolymer film are each independently selected from ethylene tetrafluoroethylene film and polytetrafluoroethylene film, The upper fluoropolymer film and the lower fluoropolymer film are used under ambient conditions, having a breaking elongation (ε) in either the longitudinal or transverse direction of 400-700%, particularly in the range of 450-650%, at a speed of 8 mm / second.

2. The aforementioned fluoropolymer film is - Melting temperature of approximately 240°C or higher (T 溶融 ), - Thickness (t) in the range of approximately 10 microns to approximately 200 microns, especially approximately 20 microns to approximately 150 microns, and particularly approximately 30 microns to approximately 100 microns. - Elastic modulus (E) in the range of approximately 300 to approximately 950 MPa, preferably in the range of approximately 350 to approximately 900 MPa, and - The use according to claim 1, having a tensile strength (σ) in the range of approximately 30 to approximately 90 MPa, preferably in the range of approximately 35 to approximately 80 MPa.

3. The use according to claim 1, wherein the upper fluoropolymer film and the lower fluoropolymer film are the same film.

4. The use according to claim 1, step (e) comprising partially closing the gap between the male and female molds such that a smaller gap is formed between the male and female molds, the smaller gap being closed after a certain time or viscosity is reached.

5. The use according to claim 1, wherein the male mold and the female mold are maintained at a temperature above the ambient temperature.

6. The use according to claim 5, wherein the male mold and the female mold are maintained at a temperature above 100°C.

7. The use according to claim 1, further comprising step (e) closing the gap between the male and female molds at a speed of about 0.7 mm / second to about 400 mm / second while maintaining the male and female molds at a temperature above the softening point of the composite material.

8. The upper fluoropolymer film and the lower fluoropolymer film are held together by a structural frame including an uppermost frame, a central frame, and a bottom frame, where, The lower fluoropolymer film is held between the bottom frame and the central frame, The upper fluoropolymer film is held between the central frame and the uppermost frame. The use described in claim 1.

9. The use according to claim 8, wherein the central frame supplies a vacuum source to the assembly.

10. The use according to claim 1, wherein the upper fluoropolymer film and the lower fluoropolymer film are held together by a structural frame including an uppermost frame and a bottom frame, and both the lower fluoropolymer film and the upper fluoropolymer film are held between the bottom frame and the uppermost frame.

11. The use according to claim 1, wherein the layered structure is placed in the press tool and in an optional heating device by automated means.

12. The use according to claim 1, wherein the composite material comprises structural fibers of materials selected from aramid, high-elasticity polyethylene (PE), polyester, poly-p-phenylene-benzobisoxazole (PBO), carbon, glass, quartz, alumina, zirconia, silicon carbide, basalt, natural fibers, and combinations thereof.

13. The use according to claim 1, wherein the composite material comprises a binder or matrix material selected from thermoplastic polymers, thermosetting resins, and combinations thereof.

Citation Information

Patent Citations

  • Performing method of composite material C-shaped component

    CN104441697A

  • Method of molding molding structure

    JP1980146710A

  • Manufacture of decorated body

    JP1985082334A

  • Gas permeable mold releasing material

    JP1994031744A

  • Molded composite assembly and method for manufacturing the same

    JP2012508662A